PENINGKATAN KETERAMPILAN SOSIAL MELALUI METODE BERMAIN PERAN USIA 5-6 TAHUN TK GEMBALA BAIK PONTIANAK - Angela, Desi; Syukri, Syukri; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was movitated by lack of social skills in 5-6 year student in one class who amounted to 20 children with 2 teachers. The purpose of this study aims to enhance the development of the child?s social skills through role play activites in children aged 5-6 years in Gembala Baik kindergarten. Social skills are very important for each person to be able to interact with environtment. Therepore social skills need to be improved since an early age. This research is a classroom action research. The subject in this study is children aged 5-6 years in group B of Gembala Baik kindergarten. The variables of this study are the social skills of the children. Data collection is done through observation and interview. The technique of data analysis was done in descriptively. The stages of the research consist of done in descriptively. The stages of the research consist of olanning, action, observation, and reflection, this study implemented as many As 2 cycles. The results showed that the social skills of children can be as 2 cycles. The result showed that the social skills of children can be increased after the given action, as for the action given a role ?play activity. Social skills, develop in the aspect of children patienty waiting for their. Turn to reach 100%, the aspect child can obey the rules that was agreed upon reaches 100%, and aspect of children work together with friends to reach 90% in cyle 2 meeting 2. Thus, social skills can be enhanced through role-play activites. Keywords: Social Skill, Role Play